Poetry and painting in Song China : the subtle art of dissent - Murck, Alfreda (Harvard-Yenching Institute monograph series., 2000)
"By examing literary archetypes, the titles of paintings, contemporary inscriptions, and the historical context, Alfreda Murck shows that certain paintings expressed strong political opinions. The message in some of these paintings was relatively transparent; in others the message was so deliberately concealed that only those with wide-ranging knowledge of literature, particularly poetry and its modes of conveying dissent and criticism, would have been able to decode it. Beyond alluding to poetry in painting, some scholars emulated the conventions of verse in structuring their paintings, further strengthening the bond between text and image. Murck argues that the coding of messages in seemingly innocuous paintings was an important factor in the growing respect for painting among the educated elite and that the capacity of painting's systems of reference to allow scholars to express dissent with impunity contributed to the art's vitality and longevity."--Back cover